Digital Accounting Literacy in Vocational Students: The Mediating Role of Learning Motivation between Self-Regulated Learning and Emotional Intelligence - Amir Mahmud; Nurdian Susilowati; Lyna Latifah; Puji Novita Sari (Universitas Pendidikan Ganesha, 2025)
In the digital era, vocational accounting students are expected to master not only accounting concepts but also digital competencies to support workplace readiness. However, many students still lack adequate digital accounting literacy, which hinders their ability to adapt to technology-based learning and practices. This study addresses how internal student factors, such as self-regulated learning and emotional intelligence, influence digital literacy skills, with learning motivation as a mediating variable. The research employed a quantitative approach with a survey design involving 140 accounting students selected through proportional random sampling. Data were collected via online questionnaires and analyzed using path analysis. The results indicate that self-regulated learning has a direct effect on digital literacy skills, while emotional intelligence does not. Learning motivation directly influences digital literacy skills and mediates the indirect effects of both self-regulated learning and emotional intelligence. These findings suggest that fostering self-regulation and motivation is essential for enhancing students' digital competencies. These results imply that schools and educators should design targeted interventions, such as digital-based learning modules and motivation-enhancing strategies, to strengthen students’ digital literacy in vocational accounting education.